Developing and testing community-based tuberculosis (TB) screening intervention to increase TB referral, case detection and knowledge among sexual minority people in urban Bangladesh: a mixed-method study protocol - Mahbubur Rahman; Golam Sarwar; Masud Reza; Mohammad Niaz Morshed Khan; Gorkey Gourab; A K M Masud Rana; Shaan Muberra Khan; Samira Dishti Irfan; Shahriar Ahmed; Rupali Sisir Banu; Sayera Banu; Sharful Islam Khan (BMJ Open, 2020)
Introduction Although Bangladesh is a country of generalised tuberculosis (TB) epidemic, the HIV prevalence is low among general populations, and 3.9% among key populations. Despite the high possibility of HIV–TB coinfection, scientifically tested approaches for increasing TB case detection among sexual minority people are yet to be developed and implemented in Bangladesh. Such approaches could foster service delivery linkages between communities and the government health system. Findings of this experimental research are likely to provide new insights for programme managers and policy planners for adopting a similar approach in order to enhance TB referral, thus ultimately increasing TB case detections and reducing the likelihood of TB-related mortalities and morbidities, irrespective of HIV status.Methods and analysis This operational research will follow a quasi-experimental design, applying both qualitative and quantitative methods, in two drop-in centres in three phases. Phase 1 will encompass baseline data collection and development of a community-based TB screening approach. In phase 2, the newly developed intervention will be implemented, followed by end-line data collection in phase 3. Qualitative data collection will be continued throughout the first and second phases. The baseline and end-line data will be compared both in the intervention and comparison areas to measure the impact of the intervention.Ethics and dissemination Ethical approval was obtained from the Institutional Review Board of International Centre for Diarrhoeal Disease Research, Bangladesh. The findings will be disseminated through diverse scientific forums including peer-reviewed journals, presentation at conferences and among the policy-makers for policy implication. The study started in January 2019 and will continue until June 2020.